Eelgrass beds and bare substrata – sparid and mugilid composition in contrasting littoral estuarine habitats. Issue 2 (3rd April 2017) - Pollard, M; Hodgson, AN; Kok, HM; Whitfield, AK
Abstract : Seagrass beds serve as nursery grounds for many fish species and often play an important role in the juvenile stages of economically and recreationally important fishes. The eelgrass Zostera capensis is the dominant submerged macrophyte in permanently open South African estuaries and occupies large intertidal and subtidal areas within the Knysna system. The primary objective of this study was to compare the occurrence of sparids and mugilids in eelgrass and nearby bare sediment areas using sampling with seine nets. The hypothesis that was tested is that mugilids are dominant in unvegetated areas of the Knysna Estuary littoral whereas sparids predominate within eelgrass beds located in the same zone. The results indicate that the family Mugilidae is better represented at unvegetated sites when compared to members of the family Sparidae, with the exception of Lithognathus lithognathus, but that the dominant three sparids and dominant two mugilids were most abundant in sparse eelgrass beds that included both bare and vegetated areas within this habitat type. The main fish species responsible for the separation of fish assemblages associated with unvegetated sites versus those associated with vegetated areas were Rhabdosargus holubi, Liza dumerili, Liza richardsonii, Lithognathus lithognathus, Sarpa salpa and Diplodus capensis, with R. holubi, S. salpa and D. capensis being mainly attracted to eelgrass habitats and L. dumerili, L. richardsonii and L. lithognathus having a stronger affinity for bare areas. This finding confirms a previous estuarine study in the nearby Swartvlei lake littoral, which found that sparids dominated areas where aquatic macrophytes were extensive and that mugilids became more prevalent at those same sites when the macrophytes underwent complete senescence. The length-frequency distributions of some sparid and mugilid species differed considerably between eelgrass and bare sediment areas, whereas those of other species showed little or no difference between these two habitat types.